Analysis of serum immunoglobulin G (IgG) levels against Toxoplasma Gondii, herpes simplex virus types 1 and 2, cytomegalovirus and hepatitis C virus in vitiligo - Rachel de Paula S Ribeiro; Kenia A. P Lacerda; Lídia A Guillo (Wolters Kluwer Medknow Publications, 2023)
Background: Pathogen infections have been associated with autoimmunity, which in turn has been implicated in the pathogenesis of vitiligo. However, the association between pathogen infections and vitiligo remains elusive. Aims: This study aimed to assess the proportion of individuals who tested positive for specific IgG antibodies against selected pathogens in patients with vitiligo and control subjects. Materials and Methods: Plasma from 51 patients with vitiligo and 51 age- and gender-matched controls were tested for anti-Toxoplasma gondii (T. gondii) IgG, anti-herpes simplex types 1 and 2 (HSV-1/2) IgG, anti-cytomegalovirus (CMV) IgG and anti-hepatitis C virus IgG. Results: Among all participants (n = 102), 63%, 84% and 87% tested positive for anti-T. gondii, anti-HSV-1/2 and anti-CMV IgG antibodies, respectively. Anti-hepatitis C virus IgG was negative in all samples tested. Positive anti-T. gondii IgG was detected in plasma samples of 39 (78%) patients with vitiligo and 25 (49%) controls (odds ratio [OR] 3.68, 95% confidence interval [CI] 1.55-8.76, P = 0.0036). Anti-HSV-1/2 IgG was detected in samples of 47 (92%) patients with vitiligo and 38 (76%) controls (OR 3.71, 95% CI 1.11-12.44, P = 0.031). Differences in frequencies of positive results for anti-T. gondii IgG and anti-HSV-1/2 IgG were only significant in samples from female patients with vitiligo when compared with controls (P = 0.036 and 0.024, respectively). Anti-CMV IgG was detected in samples from 46 patients with vitiligo (90%) and 41 (84%) controls (P = 0.384). Conclusions: T. gondii IgG and HSV-1/2 IgG were significantly more frequent in patients with vitiligo, especially in women, when compared with age- and gender-matched controls. Since T. gondii and HSV-1/2 infections can trigger autoimmune events, past exposure to these pathogens may be a risk factor for the development of vitiligo.